ANALISIS DAMPAK KERJASAMA PERTAMINA DENGAN ROSNEFT TERHADAP PERTAMINA TAHUN 2015-2019 (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research focuses on the cooperation in energy sector between Pertamina and Rosneft Oil Company from Russia, this cooperation is about the building of oil refinery in Tuban, East Java. Through this cooperation, in oil and natural gas that costs big amount of accomodation, there will be further analysis on how this cooperation between Pertamina and Rosenft will impact Pertamina’s income.This research is done by using Neo-liberalisme perspective in international cooperation theory, seen from group level analysis to understand group’s behaviour in international system. The datas motsly sourced from legal website of Pertamina, Rosneft, and Indonesia’s Ministries.The result of research shows that the cooperation between Pertamina and Rosneft in the building of oil refinery in Tuban, East Java, giving significant impacts in many sectors in Indonesia. The existence of Tuban oil refinery that will be finished in 2024, is giving big contribution in energy sector infrastructure, the increase of tax and dividen to Indonesia from Pertamina, the increase of Tuban’s people life quality, the increase of knowledge in energy sector, complete Indonesia’s need of energy in the future, and increase Indonesia’s market in South East Asia.Keywords: International Cooperation, Pertamina, Rosneft Oil Company, Oil, Tuban Refinery.